Helix Health : deildarvaki - Elsa Rún Ólafsdóttir 2000-; Hrafnhildur Finnbogadóttir 2000-; Katrín Ósk Kristinsdóttir 1999-; Líneik Sóley Guðmundsdóttir 2000- (2024)
Deildarvaki is a healthcare software application widely used in healthcare institutions in Iceland. Deildarvaki displays essential patient information, aiding healthcare professionals in managing patient care efficiently. The current technology stack is outdated, prompting the need for an update. This project aims to modernize Deildarvaki while retaining its functionality. The team faced challenges with limited experience in certain technologies and connecting to the backend server. Despite these challenges, the team successfully developed a beta version of Deildarvaki and gathered user feedback for further enhancements. This report discusses the process of modernizing Deildarvaki, detailing the challenges encountered, the solutions implemented, and the outcomes achieved. The technical aspects of the project, including the development environment and tools used are discussed. The importance of user feedback in refining the application’s functionality and user experience is highlighted. Furthermore, potential areas for improvements to Deildarvaki are discussed. Overall, this project not only contributed to the advancement of Deildarvaki but also provided valuable insights into digital health solutions and enhanced the team’s skills in Next.js, React, and TypeScript.